1998
DOI: 10.1021/jf970062h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Insect Growth Regulatory Activity of Alkoxy-Substituted Benzaldoxime Ethers

Abstract: Alkoxy-substituted benzaldoxime ethers, namely (i) 3-methoxy-4-ethoxybenzaldoxime N-O-alkyl ethers, (ii) 3,4-dimethoxybenzaldoxime N-O-alkyl ethers, and (iii) 3,4-methylenedioxybenzaldoxime N-O-alkyl ethers, have been synthesized and evaluated for their insect growth regulatory activity against fifth-instar nymphs of the desert locust Schistocerca gregaria F. When injected into insect hemolymph at the lowest dose level of 3 µg/nymph, 3,4-methylenedioxybenzaldoxime N-O-methyl ether and 3,4-methylenedioxybenzald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…On the other hand, limited biological activity studies on bis- benzofuran containing compounds were found [ 3 , 5 , 7 ]. As is known, oxime ethers have found many uses in recent years as nonsteroidal antinflammatory drugs [ 8 ], beta-adrenergic [ 9 ], mold inhibitory active compound in poultry science [ 10 ], anti-protozoan [ 11 ], insect growth regulator [ 12 ] and as various materials with steroidal effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, limited biological activity studies on bis- benzofuran containing compounds were found [ 3 , 5 , 7 ]. As is known, oxime ethers have found many uses in recent years as nonsteroidal antinflammatory drugs [ 8 ], beta-adrenergic [ 9 ], mold inhibitory active compound in poultry science [ 10 ], anti-protozoan [ 11 ], insect growth regulator [ 12 ] and as various materials with steroidal effects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the large number of oximine compounds, piperonal oxime N-O-alkyl ether exhibited insecticide synergistic activity far greater than that of piperonyl butoxide [9]. Several of these also exhibited anti-insect properties against Dysdercus kocnigii [10] and Schistocerca gregaria [11]. Chowdhury et al synthesized alkoxy-substituted benzaldoxime ethers and evaluated their IGR activity against the desert locust (S. gregaria) [11].…”
mentioning
confidence: 99%
“…Several of these also exhibited anti-insect properties against Dysdercus kocnigii [10] and Schistocerca gregaria [11]. Chowdhury et al synthesized alkoxy-substituted benzaldoxime ethers and evaluated their IGR activity against the desert locust (S. gregaria) [11]. On topical application (at 20 µg/nymph), the most active 3-methoxy-4-ethoxybenzadoxime-N-methyl ether, caused 100% deformity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Oxime ethers also undergo many organic transformations in organic synthesis 4 and were used as intermediates in the synthesis of a variety of amino acids. 5 In addition, substituted oximes ethers have been found to have insect growth regulatory activity 6 and have application as insecticides, acaricides, and agrochemical fungicides. 7 In our continuing investigation of the sequential transformations of phosphonates in organic synthesis, [8][9][10] we report here, the sequential transformation of vinylphosphonate and its application to the synthesis of ethoxycarbonyl allyl substituted oxime ethers (Scheme).…”
mentioning
confidence: 99%